Museum Storage Facilities in the Netherlands: The Good, the Best and the Beautiful. Issue 1 (2nd January 2021) - Ankersmit, Bart; Loddo, Marzia; Stappers, Marc; Zalm, Cindy
Abstract: Despite the fact that the Netherlands is a small, centralised country, its storage facilities are surprisingly diverse. What has led to the development of such different storage solutions? In order to address this question, we followed three lines of investigation. Firstly, a survey was conducted to evaluate stored collections in the Netherlands. Secondly, a selection of facilities were visited to investigate the evolution of storage buildings, systems and collection management. Thirdly, to inform future decision-makers, a quantitative benchmark was created by evaluating key data on floor areas, objects and costs. This article discusses the evolution of storage in the Netherlands in terms of sustainability, access, climate control and location. Each facility was developed with objectives specific to its time and relevant for the stakeholders of that project. Over time, project stakeholders, objectives and ambitions changed. Political and economic drivers formed the basis for shared storage facilities in which different functionalities to work with or study the collection are available. When budgets were cut and sustainability became a global issue, a shift towards low-energy buildings occurred. Over time, Dutch museums became aware of their societal roles and their accountability as treasurers of the nation's heritage. Collection centres were created to foster connections with the public and to legitimise the vast numbers of stored collections. This study shows that in order to develop new storage facilities that are economically, socially and financially sustainable, attention must be paid to longer term objectives for such buildings.